(untitled) (Zdravstveni glasnik, 2024)
Introduction: The term low back pain means a feeling of pain at rest or during movement in the lower, lumbar part of the spine. In order to reduce pain, various physical procedures are used: electrotherapy, thermotherapy, laser therapy, magnetotherapy, ultrasound therapy, cryotherapy, kinesitherapy and manual massage. Aim: To examine the effectiveness of magnetotherapy in the treatment of patients with lumbar syndrome. Materials and Methods: The study included patients treated from 01.01.2013. to 31.12.2015. year due to the diagnosis of lumbar pain syndrome in persons whose treatment process included magnetotherapy in the "Beljan" practice as a research group where were treated 113 patients (73 male and 40 female). There were 262 (114 male and 148 female) patients in the Health Center in Metković as a control group in which magnetotherapy was not included in the treatment of any patient. Pain was assessed on the basis of a visual analogue scale. Results: Research showed that the Chi-square test showed a statistically significant difference between the duration of physical therapy by days between the examined and control groups, χ2(2,n=375) = 237.715; p<0.001. Pearson’s correlation coefficient r=0.68 shows a large statistical difference between the duration of physical therapy of the examined and control groups. The chi-square test showed a statistically significant difference between the kinesitherapy procedures and the examined or control group, χ2(2,n=375) = 28.743; p<0.001. Pearson’s correlation coefficient r=-0.156 shows an extremely small statistically significant difference between the tested and control groups and kinesitherapy procedures. Conclusion: The shortest time that the patients spent on physical therapy in the examined group (80 patients) is 0 - 6 days of therapy, the shortest, and in the control group (197 patients) it is 7 - 10 days, the shortest. The working hypothesis that magnetotherapy affects the duration of treatment and the improvement of the functional status of patients with lumbar syndrome has been proven